ANALISIS KINERJA GRAND TEMBAGA HOTEL DENGAN METODE BALANCE SCORECARD - Depi Puspita; Ignasius Narew (CV. ADIBA AISHA AMIRA, 2023)
The purpose of this study is to determine the level of performance of the Grand Copper Hotel based on financial and non-financial aspects. In addition, the results of this study can be used as a reference for companies to determine the right strategy in achieving company goals. This research is a descriptive research with primary and secondary data sources. Data collection techniques in this study were through interviews, observation and documentation. Data analysis techniques in research for financial aspects are used Current ratio, Net Profit Margin (NPM) and Return On Assets (ROA) Ratio. Furthermore, for non-financial aspects using a customer perspective (Customer Retention, Customer Acquisition and Number of Complaints), internal business perspective (Speed of employees serving customers) and Learning and Growth perspective (Employee Trunover and Employee Training). The results of this study indicate that the Performance Analysis of the Grand Copper Hotel Company from 2019-2021 based on the financial aspect is categorized as unfavorable, while on the non-financial aspect the company's performance has been quite good